Lunar regolith thickness estimation using dual frequency microwave brightness temperature and influence of vertical variation of FeO+TiO2. (January 2015) - Vijayan, S.; Mohan, Shiv; Murty, SripadaV.S.
Abstract: Desiccated lunar regolith emits substantial amount of radiation in microwave region, which can be used to decipher regolith thickness distribution. We have evolved a dual frequency microwave brightness index for the estimation of regolith thickness using simulated passive microwave brightness temperature ( T B ) expected from Chandrayaan-2 at L (1.25 GHz)- and S (2.1 GHz)-bands. We used a three-layer model to simulate T B by varying the dominant parameters like bulk density ( ρ ), dielectric permittivity and FeO+TiO2 ( S ) content. The inversion of regolith thickness is carried out using simulation of T B for both the frequencies under a variety of ρ and S contents. Subsequently, a first order empirical model for regolith thickness estimation is evolved using a new dual frequency index involving both the T B . Inverted regolith thickness has been shown to be in good agreement with in-situ measurements at Apollo regions, using single (L-band) and dual frequency index. Inverted thickness for the Apollo14 and Apollo17 locations differ from mare and highland region estimation, which is further analysed to elucidate the role of vertical variation of FeO+TiO2 content. With the FeO+TiO2 variation vertically by ±1–2 wt%, the first order assessment of estimated regolith thickness is found to vary by 0.5 m and 1 m, respectively, by single- and dual-frequency approaches. Impact basin ejecta (Apollo14) and mare-highland transition region (Apollo17) are probable zones where vertical variation of FeO+TiO2 occurs along with lateral variations. This lateral- and vertical-mixing of FeO+TiO2 may influence the emitted T B from lunar regolith. Highlights: Dual frequency index based first order model developed to compute regolith thickness. Model validated to Apollo locations, estimated regolith thickness in plausible limits. Effects of vertical variation of FeO+TiO2 on regolith thickness is evaluated. Apollo 14, 17 regolith estimation influenced by vertical variation of FeO+TiO2 .